Sovereignty Dynamics In The US-China Geopolitical Conflict In The South China Sea - Muhammad Budiana; Bedi Budiman (SEAN Institute, 2024)
The South China Sea is a strategic area rich in natural resources and international trade routes, making it a hot spot in global geopolitical conflicts. This research analyzes the dynamics of sovereignty in the geopolitical conflict between the United States (US) and China in the South China Sea. This research uses a qualitative approach with descriptive analysis methods to examine how the two countries utilize their sovereignty claims as a tool to strengthen their respective political and economic positions in the region. The research results show that shifts in the understanding of maritime sovereignty have created significant challenges for regional and global stability, especially in the South China Sea. Different interpretations of sovereignty and maritime rights between major powers such as the United States and China, as well as ASEAN countries, have blurred traditional boundaries and increased regional militarization. This research finds that to overcome the emerging tensions, innovative maritime diplomacy approaches are needed, the development of new conflict resolution mechanisms, and the possibility of redefinition of the concept of sovereignty to be more inclusive and adaptive. This approach is expected to create solutions that maintain a balance between national sovereign rights and global stability, as well as ensuring compliance with international legal principles.